Ephemeral Content and Ephemeral Consumption on TikTok - Caliandro, Alessandro; Gandini, Alessandro; Bainotti, Lucia; Anselmi, Guido (The Platformisation of Consumer Culture, 2024)
In this chapter, we look at how TikTok's templates and algorithmic logics are incorporated into users' everyday practices of content production and of interaction within the platform itself. In doing so, we analyse how TikTok's architecture prompts practices of ephemeral consumption, here intended as forms of ephemeral digital consumption (rather than other forms of fast-paced and temporary consumption, such as fast fashion). By mixing hashtag analysis, sound analysis, and the visual analysis of TikTok videos, this chapter illustrates how platform affordances can stimulate the emergence of ephemeral consumption practices. By focusing on one TikTok challenge, the #shoechallenge, results show that ephemeral consumption on TikTok is characterised by: a) the ubiquitous display of consumption; b) the limited temporality of video clips; c) the situational nature of users' performances; and d) the attempts at attention-seeking in an algorithmically mediated and memetic platform.